2014
DOI: 10.4236/ape.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Physiques in Migrant Peasant Worker’s Children by Comparison with Rural and Urban Children in Shanghai, China

Abstract: Background: a few studies have been conducted which describe health status of Migrant Peasant Worker's children. However, there are no studies which compare physiques of MPW's children with those of rural children and urban children. Also, few studies have been done on physiques of MPW's children as it relates to socioeconomic factors in China. Methods: We examined across-sectional study of 2457 children from Shanghai and Wuhu city in 2011. First, we compared the differences of physiques among three groups by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In regard to MC, these authors applied a rope skipping test and found better performances in the boys from urban environment, but not in the girls, who performed on the same level as the girls from the rural site. In studies by Lu et al [ 118 ], performance was found to be superior in urban and metropolitan environments, whereas Zhu et al [ 27 ] did not find differences in children and adolescents living in either rural or urban communities. In Germany, Golle et al [ 45 ] diagnosed children from rural areas to be superior in PF and MC.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to MC, these authors applied a rope skipping test and found better performances in the boys from urban environment, but not in the girls, who performed on the same level as the girls from the rural site. In studies by Lu et al [ 118 ], performance was found to be superior in urban and metropolitan environments, whereas Zhu et al [ 27 ] did not find differences in children and adolescents living in either rural or urban communities. In Germany, Golle et al [ 45 ] diagnosed children from rural areas to be superior in PF and MC.…”
Section: Discussionmentioning
confidence: 99%
“…temperature ranges from -10 °C to -32 °C. Summer, which is short at approximately 1-2 months, is not very hot, and the average monthly temperature ranges from 16 (2) There was nine measurement items for both boys and girls, namely, height (cm), weight (kg), BMI (kg/m2), vital capacity (ml), 50 m sprint (s), sit and reach (cm), 50m × 8 shuttle run (s), timed sit-…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…The flow of rural labor in China began in the early 20th century, and experienced a phased change in scale. With the acceleration of rural economic development, urban reform and the process of opening to the outside world, it reached a climax [1][2]. In the early 20th century, migrant workers were less than ten thousand people, more than ten thousand people in recent years, and then increased to 10000 after the year.…”
Section: Introductionmentioning
confidence: 99%